Action of ear acupuncture in people with chronic pain in the spinal column: a randomized clinical trial - Caroline de Castro Moura; Denise Hollanda Iunes; Silvia Graciela Ruginsk; Valéria Helena Salgado Souza; Bianca Bacelar de Assis; Erika de Cássia Lopes Chaves (Universidade de São Paulo, 2018)
ABSTRACT Objectives: to assess the action of ear acupuncture on disability and tissue temperature in people with chronic pain in the spinal column. Method: a clinical trial with a sample of 110 people, randomized into three groups: Treatment, Placebo and Control. The assessment instruments were the Rolland Morris Disability Questionnaire (RMDQ) and a thermographic camera, administered before the first treatment session, one week after and 15 days after (follow-up) the fifth session of ear acupuncture. In the analysis of the data, the Kruskal Wallis, Student-Newman Keuls and Wilcoxon tests were applied. Results: there was a significant reduction in disability in the Treatment and Placebo groups between the initial and final assessments (p<0.05) and between the initial assessments and follow-up (p<0.05). In the final assessment, the Treatment group presented improvement of disability when compared with the Placebo and Control groups (p<0.05). There was an increase in mean tissue temperature of the dorsal region between the initial and follow-up assessments in Treatment and Control groups (p<0.05), and between the final assessments and follow-up in the Treatment and Placebo groups (p<0.05). Conclusion: ear acupuncture was efficacious in reducing disability and increasing tissue temperature in people with chronic pain in the spinal column. Brazilian Register of Clinical Trials (RBR-5X69X2).